Correction to: The misruling elites: the state, local elites, and the social geography of the Chinese Revolution (Theory and Society, (2024), 53, 2, (465-508), 10.1007/s11186-023-09536-1) - Xu, X (Springer Science and Business Media LLC, 2024)
10.1007/s11186-024-09548-5